2017
DOI: 10.1093/mnras/stx1698
|View full text |Cite
|
Sign up to set email alerts
|

AGN jet-driven stochastic cold accretion in cluster cores

Abstract: Several arguments suggest that stochastic condensation of cold gas and its accretion onto the central supermassive black hole (SMBH) is essential for active galactic nuclei (AGN) feedback to work in the most massive galaxies that lie at the centres of galaxy clusters. Our 3-D hydrodynamic AGN jet-ICM (intracluster medium) simulations, looking at the detailed angular momentum distribution of cold gas and its time variability for the first time, show that the angular momentum of the cold gas crossing 1 kpc is es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 60 publications
(84 reference statements)
1
45
0
Order By: Relevance
“…In Figure 14, we note that the prominent optical filaments of the cluster are oriented toward the potential ghost cavities. Optical filaments are thought to be created from thermally unstable ICM gas (e.g., McCourt et al 2012;Sharma et al 2012;Gaspari et al 2013b;Li & Bryan 2014a, 2014b) that originates, in part, from the pushing-back motions created by the formation of X-ray cavities (e.g., McNamara et al 2016;Hogan et al 2017;Prasad et al 2017;Voit et al 2017;Gaspari et al 2018). Therefore, filaments could have been created in the wake of the cavities (e.g., Hlavacek-Larrondo et al 2013a), and thus the observed optical filaments in MACS J1447.4+0827 Figure 11.…”
Section: Optical Filaments Ghost Cavities and The Plumementioning
confidence: 99%
“…In Figure 14, we note that the prominent optical filaments of the cluster are oriented toward the potential ghost cavities. Optical filaments are thought to be created from thermally unstable ICM gas (e.g., McCourt et al 2012;Sharma et al 2012;Gaspari et al 2013b;Li & Bryan 2014a, 2014b) that originates, in part, from the pushing-back motions created by the formation of X-ray cavities (e.g., McNamara et al 2016;Hogan et al 2017;Prasad et al 2017;Voit et al 2017;Gaspari et al 2018). Therefore, filaments could have been created in the wake of the cavities (e.g., Hlavacek-Larrondo et al 2013a), and thus the observed optical filaments in MACS J1447.4+0827 Figure 11.…”
Section: Optical Filaments Ghost Cavities and The Plumementioning
confidence: 99%
“…We found that radio jets were closely correlated with declining central temperature profiles and, where it could be calculated, low minimum values of the ratio of the cooling time to the free fall time in the IGM, min(t c /t f f ) 15. This link with jet activity suggests that at low values of this instability criterion, cooling from the IGM produces sufficient cold material to fuel the AGN (see also Valentini & Brighenti 2015;Prasad et al 2015Prasad et al , 2017Prasad et al , 2018. The jet systems also had low central cooling times and entropies, but so did a number of systems without evidence of recent AGN outbursts.…”
Section: Thermal Instabilitymentioning
confidence: 99%
“…Over the past decade, extensive investigations have been carried out in order to understand the mechanism through which AGN inject energy into the surrounding medium and how the condensed filaments/clouds form out of the hot halos (Gaspari et al 2009(Gaspari et al , 2011a(Gaspari et al ,b, 2017Pizzolato & Soker 2010;McCourt et al 2012;Sharma et al 2012;Li & Bryan 2014;Prasad et al 2015Prasad et al , 2017Voit et al 2015aVoit et al , 2017Valentini & Brighenti 2015;Soker 2016;Yang et al 2019). A novel paradigm has emerged in which the AGN feedback cycle operates through chaotic cold accretion (CCA; Gaspari et al 2013Gaspari et al , 2015, where turbulent eddies induced by AGN outflows (and cosmic flows; Lau et al 2017) are responsible for the condensation of multiphase gas out of the hot halos via nonlinear thermal instability.…”
Section: Introductionmentioning
confidence: 99%